The effect of vocal warm-up on voice quality of untrained female singers in Malaysia / Ter Wei Shean - Ter , Wei Shean (2020)
Professional singers and singing teachers regard vocal warm-up as vital. However, very few studies have evaluated this effect quantitatively. This study aimed to evaluate the effect of the vocal warm-up on the singing voice quality through acoustic parameters of Jitter, Shimmer and harmonics-to-noise ratio (HNR) and to assess whether scientific evidence supports the warm-up procedure, whether an untrained singer can benefit from singing vocal warm-up exercises in a similar way as a trained singer and whether the vocal warm-up should be encouraged or bypassed. 40 untrained female singers were recorded twice while uttering the vowel /a/, /o/ and /i/ in two different pitches: Low- A3 (220.0 Hz) and High- C5 (523.2 Hz) for at least five seconds. The recordings were collected before and after a 20 minutes vocal warm-up session. Results showed significant variations in the average values of the parameters measured. A decrease was detected in comparison with the average value of Jitter and Shimmer before and after the vocal warm up, whereas HNR increased. The results of this study provide valid support for the advantageous effect of vocal warm-up on the voice quality of untrained female singers and present acoustic analysis as a valuable and sensitive tool for quantifying this effect. The positive effects of the findings indicated that the vocal warm-up should be encouraged and not bypassed. As for the vowel effect, per cent jitter, per cent shimmer and harmonics-to-noise ratio (HNR) may not be useful for the description of acoustic differences between vowels.